Changes in optic nerve sheath diameter and its correlation with degree of consciousness, pupil diameter, and light reflex in children with central nervous system infection after osmotherapy - Rizqiamuti, Anggia F.; Risan, Nelly A.; Solek, Purboyo; Hakim, Dzulfikar D. L.; Nugraha, Harry G.; Hawani, Dewi; Dewi, Mia M.; Herini, Elisabeth S. (Frontiers in Pediatrics, 2024)
Background High intracranial pressure (ICP) is one of the most common complications of central nervous system (CNS) infection. Failure to control high intracranial pressure results in brain herniation and death. One of the treatments for high ICP involves the administration of osmotherapy in the form of 3% NaCl or 20% mannitol with observation during administration. Observation of ICP during administration of osmotherapy is possible through measurement of optic nerve sheath diameter (ONSD), which could be correlated with degree of consciousness, pupil diameter, and light reflex. Previous studies have not correlated ONSD with degree of consciousness, pupil diameter, and light reflex during the administration of osmotherapy. Purpose To provide insights of incorporating ONSD measurement as a form of non-invasive bedside method for ICP monitoring by correlating it with degree of consciousness, pupil diameter, and light reflex at several time points. Methods This study is a prospective cohort study, performed at Dr. Hasan Sadikin General Central Hospital Bandung, Cibabat General Regional Hospital, and General Regional Hospital Bandung Kiwari on children aged 2–18 years with decreased consciousness and CNS infection, from June 2023. Inter-rater reliability was performed with a correlation coefficient of 0.90. Measurement of ONSD, degree of consciousness, pupil diameter, and light reflex simultaneously up to 48 h after initiation of osmotherapy to 30 patients. Correlational analyses were performed using Spearman's rank. Results Observation for 48 h after administration of osmotherapy showed changes in ONSD. A significant positive correlation was found between ONSD and degree of consciousness (r = 0.621 for the right eye and r = 0.602 for the left eye, p < 0.001). A significant positive correlation was found between ONSD and light reflex (r = 0.801 for the right eye and r = 0.812 for the left eye, p < 0.001). No significant correlation was found with changes of pupil diameter (r = −0.136 for the right eye and r = −0.141 for the left eye, p > 0.05). Conclusion A significant correlation was found between ONSD and degree of consciousness and light reflex in children aged 2–18 years with CNS infection during administration of osmotherapy.